Single CdSe/CdS colloidal nanocrystals embedded in an Ultra-Pure SiO2 matrix deposited by ion beam sputtering. (25th March 2020) - Aubret, A; Dolique, V; Piednoir, A; Dujardin, C; Kulzer, F; Houel, J
Abstract: We report the encapsulation of high-quantum-yield CdSe/CdS colloidal nanocrystals in a smooth and ultra-pure layer of SiO2 deposited by ion beam sputtering. The optical quality of the thin silica film is comparable to the mirror substrates used in gravitational-wave detection, with a density of impurities as low as a few ppm. We show that at least 30% of the nanocrystals survive the encapsulation process under full conservation of their favorable optical properties at the single-quantum-dot level, namely a high and stable emission rate combined with a short recombination lifetime. The emission rate of the embedded nanocrystals is increased by 100% due to the higher refractive index of the SiO2 film, in accordance with an effective-medium interpretation. Our device prototype thus provides a perspective for designing large-scale, high-quality and thickness-controlled light-emitting diodes based on semiconductor nanocrystals as active components in a durable inorganic matrix.